(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
the article is devoted to the analysis of a new stage of development of society, namely the information stage, increasing attention to the problems of information, knowledge accumulation, and the formation of human and intellectual capital.